Posterolateral Lumbar Fusion For Idiopathic Anterior Fusion of Lumbar Vertebral Bodies: A Case Report - Serin, Erhan; Karakurt, Lokman; Belhan, Oktay (Fırat University, 2006)
We performed bilateral posterolateral lumbar fusion in a 12-year-old girl who had disabling discogenic low-back pain associated with idiopathic anterior fusion of lumbar vertebral bodies. At the end of 2-years follow-up period, she had only minimal low back pain without disability.©2006, Fırat Üniversitesi, Tıp Fakültesi

İdiopatik lomber vertebra anterior füzyonuna bağlı diskojenik kökenli şiddetli bel ağrısı olan 12 yaşındaki kız olguda, bilateral posterolateral füzyon yapıldı. İki yıllık takib süresinin sonunda rahatsızlık vermeyen hafif bir bel ayrısı dışında sorun yoktu. ©2006, Fırat Üniversitesi, Tıp Fakültesi
İdiopatik lomber vertebra anterior füzyonunda posterolateral lomber füzyon: olgu sunumu